RITUS PURUNG TA KADONGA RATU DALAM KEPERCAYAAN MARAPU DAN RELASINYA DENGAN PERAYAAN EKARISTI - Pawolung, Martha; Midun, Hendrikus (CREDENDUM: Jurnal Pendidikan Agama, 2023)
Purung ta Kadongan Ratu is one of the rites in the Marapu belief system in Central Sumba. This rite is carried out regularly by the people of Sumba, including those who are Catholics. Does this rite have a correlation (faith) with the celebration of the Eucharist in the Catholic Church? This paper aims to find and explain the relationship between the meaning of thanksgiving in the purung ta Kagawanga Ratu rite and the celebration of the Eucharist in the Catholic Church. This study uses a qualitative approach with interviews and documentation methods. The research subjects were elders/traditional actors/heirs, community leaders, and humanists in Central Sumba, who had in-depth knowledge of the purung ta Kakaongan Ratu rite. Data analysis uses the Miles and Huberman model, which includes three stages of activity namely data reduction, data display, and making conclusions. The results of the analysis reveal that the rites of the purung ta Kangkang Ratu have similarities and differences with the celebration of the Eucharist in the Catholic Church. The similarities between these two celebrations are as a celebration of thanksgiving for the success and blessings that God has given to humans, as a celebration that unites the faithful in a communion, and as a celebration full of symbols. While the differences are in the naming of the "form" of the purpose of thanksgiving, the implementation of the rites, and the sacrificial materials used. These findings have implications for the practice of Catholic faith education and further research.